Competencies and Development Needs of Professional Nurses in Emergency and Forensic Nursing at Community Hospitals in Songkhla Province - Tuwanputeh, Arraya; Purinthrapibal, Shutiwan; Thongsuk, Pramot (Journal of Research in Nursing-Midwifery and Health Sciences, 2025)
Objectives: To assess the competency levels and competency development needs of professional nurse in emergency and forensic nursing at community hospitals in Songkhla Province. Methods: This descriptive study included 125 professional nurses working in emergency and forensic nursing departments at community hospitals in Songkhla Province, excluding department heads. The research instrument was a questionnaire divided into three parts: 1) general information, 2) competency levels, and 3) competency development needs. The content validity of part 2 and 3 was reviewed by three experts, yielding CVI values of .97 and 1.0, respectively, and reliability was confirmed with a Cronbach’s alpha coefficient of .98. Data were analyzed using mean, standard deviation, frequency, and percentage. Results: The overall competency level of professional nurses was high (M = 4.10, SD = .50), and the highest mean score among the nine categories was resuscitation competency (M = 4.10, SD = .50), with “life-saving” skills scoring the highest (M = 4.31, SD = .59). 2) The overall competency development needs were also high (M = 4.10, SD = .50), “life-saving” (M = 4.22, SD = .78), and “patient triage” (M = 4.22, SD = .69). Conclusion: Competency development plans should utilize self-assessment data from professional nurses to enhance the quality of care in emergency and forensic nursing.